The Effect Of Emotional Branding On Customer Loyalty Among Consumers Of Poci Tea In The City Of Soppeng - Asnia Minarti; Surianti Surianti; Rina Muliana Ismail (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
The research question in this study is whether emotional branding has a positive effect on customer loyalty among consumers of iced tea at The Poci in Soppeng City. This study was conducted at The Poci Police Dormitory outlet located on Jalan Samudera, Botto Village, Lalabata District, Soppeng Regency. The respondents in this study were determined using purposive sampling, which is the selection of respondents from the population based on specific criteria. The criteria for determining respondents in this study include: Respondents have made purchases at The Poci Police Asrama Store (Aspol) Soppeng at least twice, Respondents are over 17 years of age. To determine whether the marketing mix influences customer loyalty among consumers of The Poci in Soppeng City, simple regression analysis was used. From the results of the simple regression analysis, it can be concluded that emotional branding has a positive effect on customer loyalty for The Poci. This means that the better the emotional branding of The Poci, the higher the customer loyalty. Therefore, the following recommendations can be made: Further research is encouraged to include additional variables such as sensory branding, brand image, brand experience, brand attitude, and brand trust to enhance the existing body of research. For future research, other research objects could be used, such as Es Teh 2 Daun, Es Teh Jumbo, or other iced tea brands as comparators. Future research is expected to obtain more in-depth answers from respondents. This can be done through observation and direct interviews with respondents